Two new species of land flatworms and comments on the genus Pasipha Ogren & Kawakatsu, 1990 (Platyhelminthes: Continenticola) - Leal-Zanchet, Ana Maria; Rossi, Ilana; Seitenfus, Ana Lúcia Ramos; Alvarenga, Juliana (Zootaxa, 2012)
Two new species of Geoplaninae, Pasipha backesi Leal-Zanchet, Rossi & Seitenfus, sp. nov. and P. brevilineata Leal-Zanchet, Rossi & Alvarenga, sp. nov., from southern Brazil are described herein. The two new sympatric species can bedistinguished from each other by differences in colour pattern and the copulatory apparatus, especially regarding the pro-static vesicle. They show similar characteristics regarding the relative position of the ovaries and anteriormost testes inrelation to body length, the position where ovovitelline ducts emerge from the ovaries, pharyngeal morphology and gen-eral morphology of the copulatory apparatus. Comments on the most important morphological characters of the 22 speciesoriginally assigned to the genus Pasipha are presented in order to highlight the heterogeneity of the genus as well as fa-cilitate the comparative discussion of the new species. In addition, based on the current diagnosis of the genus, we propose the placement of G. cafusa into Pasipha.